San Jose State College Survival Faire
A humanities course on contemporary issues organized a Survival Faire at San Jose State College. In this view three students pose together to publicize the Survival Faire event. The male student on the right is dressed in survival gear and is wearing a gas mask. He is holding two balloons and a Survival Faire sign in attached to his clothing.